Effect of extracts from eggs of Helix aspersa maxima and Helix aspersa aspersa snails on Caco-2 colon cancer cells - Matusiewicz, Magdalena; Marczak, Karolina; Kwiecińska, Barbara; Kupis, Julia; Zglińska, Klara; Niemiec, Tomasz; Kosieradzka, Iwona (PeerJ, 2022)
Background Colorectal cancer is the third most commonly diagnosed cancer. Natural compounds, administered together with conventional chemotherapeutic agent(s) and/or radiotherapy, may be a novel element in the combination therapy of this cancer. Considering the anticancer properties of compounds derived from different tissues of various snail species confirmed earlier, the purpose of the present research was to evaluate the effect of extracts from eggs of Helix aspera maxima and Helix aspersa aspersa snails, and fractions of extracts containing particles of different molecular weights on Caco-2 human epithelial colorectal adenocarcinoma cells. Methods The extracts and fractions were analyzed for antioxidant activity, phenols and total carbohydrates using colorimetric methods. Lipid peroxidation products and glutathione in eggs were also examined using these methods. Crude protein and fat in eggs were determined. Molecular weights of egg proteins and glycoproteins were analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Astaxanthin, selected vitamins and amino acids in eggs were measured using liquid chromatography methods, and minerals by emission spectroscopy, mass spectrometry or X-ray fluorescence. The action of extracts on the cell viability was determined by the MTT (methylthiazolyldiphenyl-tetrazolium bromide) test, based on the mitochondrial oxidative activity, after 24 and 72 h of treatment. The influence of fractions on the cell viability was assayed after 24 h. The effect of extracts on the percentage of live and dead cells was evaluated by the trypan blue assay, in which live cells exclude trypan blue, while dead cells take up this dye, after 12, 24, 48 and 72 h of treatment. Their influence on the integrity of cell membranes was determined based on the activity of LDH (lactate dehydrogenase), released from damaged cells, after 24 and 72 h of treatment. Then, the effect of extracts on the content of lipid peroxidation products in cells was examined using colorimetric method, after 24 h of treatment. Their influence on types of cell death was determined by flow cytometry, after this time. Results The extracts and their fractions containing molecules <3 kDa decreased the cell viability, after 24 h of treatment. The extracts reduced the percentage of live cells (also after 48 h), increased the degree of cell membrane damage and the amount of lipid peroxidation products, induced apoptosis and reduced necrosis. Conclusions Antioxidants, phenols, lipid peroxidation products, anticancer peptides, restriction of methionine, appropriate ratio of essential amino acids to non-essential amino acids, vitamin D3, Ca, Mg, S, Cu, Mn, Zn, Se and other bioactive compounds comprised in the extracts and their additive and synergistic effects may have influenced Caco-2 cells. Natural extracts or the chemical compounds contained in them might be used in the combination therapy of colorectal cancer, which requires further research.
Keywords: Helix aspersa; Snail; Egg; Extract; Chemical composition; Colorectal cancer; Caco-2